The impact of web 2.0 on the marketing processes of restaurant businesses - Pencarelli, Tonino; Cioppi, Marco; Curina, Ilaria; Forlani, Fabio (Piccola Impresa / Small Business, 2019)
This paper analyzes the modalities whereby the restaurant industry is facing the web 2.0 evolution. To achieve this objective, the study adopts multiple approach-types (adoption of an online visibility index, fuzzy-set ideal type analysis and interviews conducted to 33 Italian restaurants). Results highlight relevant gaps between full exploitation of the web potentialities and the best results obtained by the investigated restaurants (subdivided into four different ideal-types based on their online visibility performances). From a theoretical viewpoint, the study contributes to enriching the analysis of the online visibility management applied to the restaurant sector, through the creation of an index able to measure the online performances by each restaurant in relation to competitors. In addition, the work also provides managerial implications for firms’ marketers and practitioners, by identifying possible guidelines for the adoption of a pro-active attitude in using the 2.0 tools.